Terricolous Lichens in the Glacier Forefield of the Pasterze (Eastern Alps, Carinthia, Austria) - Bilovitz, Peter O. (Phyton, 2015)
The investigation of lichens on soil, plant debris and terricolous mosses in the glacier forefield of the Pasterze yielded 35 lichen species. Placidiopsis oreades Breuss (Verrucariales) is new to Austria. Three sampling sites were established at increasing distance from the glacier, in order to compare species diversity, abundance and composition within the forefield and with four other glacier forefields of the Eastern Alps.